2019
DOI: 10.1021/acs.jpcc.9b07234
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Hydroxide-Nanohexagon-Based High-Performance Electrodes for Supercapacitors: A Systematic Investigation on the Influence of Six Different Carbon Nanostructures

Abstract: Transition-metal compounds (TMCs) such as oxides, hydroxides, and sulfides are well-known pseudocapacitive materials whose capacitance has been shown to improve by combining them with different carbon nanostructures (CNSs). Here, we report a systematic investigation on the influence of six different CNSs: single-walled carbon nanotubes (SWCNTs), functionalized and multiwalled carbon nanotubes, graphene oxide (GO), reduced GO (rGO), and graphene nanoplatelets on Ni­(OH)2 nanostructures, focusing on their electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 77 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…It can be observed that the CV curve for 2La-MnO 2 -CNThas the largest enclosed area and thus is expected to exhibit the highest specific capacitance. values were obtained at high scan rates [26,37]. However, at low scan rates due to the increase in interaction time, the electrolyte ions gets a chance to enter into the pores of the active electrode material due to prolonged exposure.…”
mentioning
confidence: 94%
“…It can be observed that the CV curve for 2La-MnO 2 -CNThas the largest enclosed area and thus is expected to exhibit the highest specific capacitance. values were obtained at high scan rates [26,37]. However, at low scan rates due to the increase in interaction time, the electrolyte ions gets a chance to enter into the pores of the active electrode material due to prolonged exposure.…”
mentioning
confidence: 94%
“…Porous carbon materials such as activated carbon 6 , CNT 7 , graphene oxide (GO) 8 , reduced GO (rGO) 9 , xerogel-like 10 , and aerogels 11 are largely applied for supercapacitor electrodes because of properties like high surface area, chemical stability, high conductivity, and stable electrochemical properties 1,2,12 . Activated carbon fibers are attractive materials for supercapacitor electrodes or other applications 13 , especially because of their flexible structure and three-dimensional arrangement comprising a continuous current path, decreasing the interparticle resistance 2,14 and increasing the surface area simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent series resistance (ESR) and charge transfer resistance (R ct ) were estimated from the total equivalent circuit using the curve fitting of the electrochemical impedance spectroscopy (EIS) plot. All the samples present a semicircle in the high-frequency region associated with the charge transfer at the interface between the electrode and the electrolyte 8 . Additionally, the vertical shape of electrodes produced at 140 and 170 minutes at a low-frequency range is attributed to the EDLC characteristic of the ions diffusion process on porous structure 56 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…to form nanohybrids. [26][27][28][29][30][31][32][33] A relatively less studied metal oxide is ceria (CeO 2 ) in spite of its dynamic redox reaction, ecofriendly features and low cost. A major drawback of CeO 2 is its poor electrical conductivity [34] that can be tuned by changing its shape and size using controlled synthetic conditions by playing with the growth parameters.…”
Section: Introductionmentioning
confidence: 99%